Sistem maklumat pergigian (Sistem berasaskan web) / Siti Hajar Othman - Siti Hajar, Othman (2003)
This system was implemented to make management tasks in Klinik Pergigian, Fakulti Pergigian, Universiti Malaya done automated. The main objective is to save their time and to make sure information that they have stored before safe. To identify the system requirement, I have an interview session with one of the lecturer from Fakulti Pergigian. I'm also doing survey with the system that have been in marketing. The system that in the marketing right now was very advance from us in Malaysia. Sistem Maklumat Pergigian was divided to 3 level of users. They are student, clerk and doctor. The information retrieval was control by using password. Database for this system was developed by using Microsoft Access. For coding, I used Active Server Pages as scripting language. Microsoft Front Page was used for design user interface.